Alteration of the Helicobacter pylori membrane proteome in response to changes in environmental salt concentration. Issue 11 (14th September 2015) - Voss, Bradley J.; Loh, John T.; Hill, Salisha; Rose, Kristie L.; McDonald, W. Hayes; Cover, Timothy L.
Abstract : Purpose: Helicobacter pylori infection and a high dietary salt intake are each risk factors for the development of gastric cancer. We hypothesize that changes in environmental salt concentrations lead to alterations in the H. pylori membrane proteome. Experimental design: Label‐free and iTRAQ methods were used to identify H. pylori proteins that change in abundance in response to alterations in environmental salt concentrations. In addition, we biotinylated intact bacteria that were grown under high‐ or low‐salt conditions, and thereby analyzed salt‐induced changes in the abundance of surface‐exposed proteins. Results: Proteins with increased abundance in response to high salt conditions included CagA, the outer membrane protein HopQ, and fibronectin domain‐containing protein HP0746. Proteins with increased abundance in response to low salt conditions included VacA, two VacA‐like proteins (ImaA and FaaA), outer‐membrane iron transporter FecA3, and several proteins involved in flagellar activity. Consistent with the proteomic data, bacteria grown in high salt conditions exhibited decreased motility compared to bacteria grown in lower salt conditions. Conclusion and clinical relevance: Alterations in the H. pylori membrane proteome in response to high salt conditions may contribute to the increased risk of gastric cancer associated with a high salt diet.